2015
DOI: 10.1007/s00508-015-0719-5
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic and prognostic value of sCD14-ST—presepsin for patients admitted to hospital intensive care unit (ICU)

Abstract: CD64 index, CRP and sCD14-ST served as good parameters to determine possible infection in patients that needed intensive care after major procedures. Values of PCT were the only ones to predict SIRS severity and could distinguish between sepsis and severe sepsis or septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 35 publications
3
36
2
2
Order By: Relevance
“…Furthermore, contrary to our findings, presepsin showed a higher specificity than CRP and PCT in diagnosing sepsis [30]. Our findings differ from those of Godnic and coworkers, who reported that presepsin exhibited a higher sensitivity than CRP and PCT, whereas CRP showed a higher specificity than PCT and presepsin in diagnosing infection, with AUCs indicating that CRP tend to perform better than PCT and presepsin in detecting infection [31]. Previous meta-analyses on the diagnostic usefulness of PCT, in comparison to CRP, reported controversial and inconsistent conclusions [18,32].…”
Section: Discussioncontrasting
confidence: 86%
“…Furthermore, contrary to our findings, presepsin showed a higher specificity than CRP and PCT in diagnosing sepsis [30]. Our findings differ from those of Godnic and coworkers, who reported that presepsin exhibited a higher sensitivity than CRP and PCT, whereas CRP showed a higher specificity than PCT and presepsin in diagnosing infection, with AUCs indicating that CRP tend to perform better than PCT and presepsin in detecting infection [31]. Previous meta-analyses on the diagnostic usefulness of PCT, in comparison to CRP, reported controversial and inconsistent conclusions [18,32].…”
Section: Discussioncontrasting
confidence: 86%
“…These data agree with Godnic M et al [21] results whose findings indicated that sCD14-ST may be a promising early diagnostic and prognostic marker in septic patients. In addition, because the sCD14-ST values were especially high in severe sepsis, and there was also positive correlation between the APACHE II scores (p = 0.016) and the presepsin values reflect the immune response to bacteria in sepsis.…”
Section: Late-onset Neonatal Sepsis (Los) Is a Life-threatening Condisupporting
confidence: 83%
“…Finally, 86 studies were included after two updated searches in February 2015 and September 2016 (Fig. 1) (Abidi et al 2008; Ahmadinejad et al 2009; Al-Nawas et al 1996; Anand et al 2015; Balc et al 2003; Barati et al 2010; Battista et al 2016; Bell et al 2003; Beqja-Lika et al 2013; Carpio et al 2015; Castelli et al 2004; Clec’h et al 2006; de Pablo et al 2013; Dorizzi et al 2006; Du et al 2003; Endo et al 2012; Farag et al 2013; Feng et al 2012; Gaini et al 2006; Garnacho-Montero et al 2014; Gerrits et al 2013; Giamarellos-Bourboulis et al 2008; Gibot et al 2004; Godnic et al 2015; Guven et al 2002; Han et al 2016; Harbarth et al 2001; Hoenigl et al 2013; Hou et al 2012, 2016; Hsu et al 2011; Ishikura et al 2014; Ivancevic et al 2008; Jekarl et al 2013, 2014; Jiang et al 2015; Kim and Zhang 2012; Kofoed et al 2007; Latour-Perez et al 2010; Lewis et al 2015; Li et al 2013a; Lin et al 2015; Matera et al 2013; Mat-Nor et al 2016; Mearelli et al 2014; Meynaar et al 2011; Miglietta et al 2015; Miller et al 1999; Muthiah et al 2007, Naeini and Montazerolghaem 2006; Oshita et al 2010; Papadimitriou-Olivgeris et al 2015; Ratzinger et al 2013; Reichsoellner et al 2014; Righi et al 2014; Rivera-Chavez and Minei 2009; Rogina et al 2014; Romualdo et al 2014; Ruiz-Alvarez et al 2009; Sakr et al 2008; Scherpereel et al 2006; Schulte et al 2011; Selberg et al 2000; Seok et al 2012; Shozushima et al 2011; Sierra et al 2004; Su et al 2012, 2013; Sungurtekin et al …”
Section: Resultsmentioning
confidence: 99%